Legal Implications in Health Services: Rights and Obligations of Medical Personnel and Patients - S.T. Kansil, Christine; Siregar, Rachel Adeline (CV. Rayyan Dwi Bharata, 2024)
Health services play an important role in fulfilling human rights, especially the right to health. In this context, health law serves to protect the rights and obligations between medical personnel and patients. Various regulations, such as Law No. 36 of 2009 concerning Health and Law No. 29 of 2004 concerning Medical Practice, regulate standards and ethics in medical services. Medical personnel are required to provide professional services and respect patient rights, such as the right to information and consent, while patients are required to provide accurate information. However, legal issues such as malpractice and violations of patient rights often occur, which shows the importance of understanding and implementing the law in health services. The era of digitalization and the pandemic also presents new challenges, such as data security and electronic medical consent. Therefore, this study discusses the legal implications in health services, highlighting the importance of education and compliance with regulations to prevent conflict and improve the quality of services. By understanding each other's rights and obligations, it is hoped that a fairer, more transparent, and quality health service system can be created.